Development learning tool modification of music and dance to increase physical development in early childhood - MG. Rini Kristiantari; I Gusti Agung Oka (Jurnal Pendidikan dan Pengajaran, 2018)
This study aims to develop and produce products that Irish Music and Dance Learning Modifications to Increase Physical Development in Early Childhood Motoric on the Jempiring Denpasar Cluster Academic Year 2015-2016. The approach used in this study is a research and development for the main purpose of this study was to develop a product such as a learning tool game modification of music and dance that is adaptable and effective in accordance with the conditions and the real needs on the ground. Ten step research approaches are modified into five steps, namely the preliminary study or needs assessment, daily activity development plan (RKPH), device prototype, test, validity, and reporting. This study carried out a preliminary study/need assessment and designing prototype learning development tools ready and eligible to practice another time. The research subject is a kindergarten teacher groups Jempiring Denpasar Bali. The research data in the form of information about the number of songs that are worthy and known children with a good and simple dance that can be used for the physical development of the child's motoric activity were collected through the literature on institutions and interviews with relevant parties. Results showed that a valid creation of a learning device in the form of (a) RKPH and (b) a simple media such modifications song lyric children ready to be tested in future studies.